Peran Kepemimpinan dalam Meningkatkan Kinerja Karyawan di Lembaga Pendidikan Islam - Rosmita Rosmita; Nasaruddin Nasaruddin; Reski Mei (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to explain the role of leadership in improving employee performance in Islamic educational institutions using a qualitative descriptive method with library research techniques. This research will explore the role of leadership in improving employee performance in an Islamic educational institution. So the point of focus is the role of leadership and employee performance. Leadership in an Islamic educational institution with various forms of its role greatly determines the development of employees within the scope of their responsibilities. The leader as a motivator encourages and increases the work motivation of employees. As a director, the leader provides clear directions and instructions in the work steps of employees. As a supervisor, the leader ensures that employees work according to the rules. As communicators, leaders establish communication. Performance measurement is used to evaluate the success or failure of the implementation of activities, programs and or policies in accordance with the goals and objectives that have been set in order to realize the vision and mission of the institution. Performance measurement includes determining the achievement of performance indicators. Performance measurement considers quantity, quality, and timeliness. To develop the four competencies (pedagogic competence, personal competence, social competence, and professional competence) there is an evaluation process for employee development through performance appraisal and educational supervision.